1972
DOI: 10.1111/j.1365-2222.1972.tb01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia

Abstract: Isolated human basophils sensitized in vitro by IgE antibody, and challenged by antigen in the absence of complement, release a substance that attracts eosinophils but not neutrophils. The anaphylactic release of the eosinophilotropic substance is accompanied by morphological changes in the basophils and release of histamine and presumptive SRS-A.The anaphylactic eosinophilotropic substance differs from that formed in fresh serum by antigen-antibody complexes. Human IgG, aggregated chemically or with antigen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…When a chemotactic factor which preferentially attracted eosinophils was shown to be released from human mast cells (8) and basophils (27,28), the activity was found to reside in peptides that could be distinguished from histamine by size, charge, and susceptibility to enzymes (6) . This factor was designated eosinophil chemotactic factor of anaphylaxis (ECF,) .…”
Section: Discussionmentioning
confidence: 99%
“…When a chemotactic factor which preferentially attracted eosinophils was shown to be released from human mast cells (8) and basophils (27,28), the activity was found to reside in peptides that could be distinguished from histamine by size, charge, and susceptibility to enzymes (6) . This factor was designated eosinophil chemotactic factor of anaphylaxis (ECF,) .…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight (300-500 daltons) eosinophil chemotactic factor (ECF) was first described in mast cells [1] and ba sophils [2], and since then, a similar ECF has been reported in human neutrophils and eosinophils (3] and more recently in murine macrophages [4).…”
Section: Introductionmentioning
confidence: 99%
“…This study also indicates a similar fiuctuation in the presence of eosinophilic granulocytes in the sputum. Parish (1972) has suggested that basophils may elaborate a substance that is chemotactic for eosinophils. The elaboration of such a chemotactic substance may explain the observed parallel fiuctuation in basophil and eosinophil numbers in the sputa of bronchial asthmatics.…”
Section: Discussionmentioning
confidence: 99%